Cyberbullying among University Students during the E-learning Transformation Era: The Role of the Student-Teacher Relationship and Virtual Classroom Community. - Sayed, Samiha; AbuElEla, Lucy; Sarhan, Ahlam; El Demerdash, Doaa (Research in Community & Public Health Nursing (RCPHN), 2023)
Purpose: The current study assesses cyberbullying among university students and explores the role of the student-teacher relationship and virtual classroom community. Methods: A descriptive exploratory study on four randomly selected colleges at Damanhour University/Egypt. Participants were recruited conveniently using an equal allocation of 150 students/college (600 students). The European Cyberbullying Intervention Project Questionnaire (ECIPQ), Rovai's Classroom Community Scale (RCCS), and the Student Version of The Teacher-Student Relationship Inventory (S-STRI) were used for data collection. Results: Low cyber victimization was reported by 66.5% of the students, while 39.8% reported low cyberaggression behaviors. The highest percent reported average virtual class connectedness (77.3%), learning experience (70.3%), and overall virtual classroom community (80.8%). Besides, highly satisfying teacher relationships (82.3%); average (38.8%) and low (35.8%) instrumental help; low conflict (68.0%); and average total teacher-student relationship (70.5%). Regression analysis revealed that the increased scores of the total teacher-student relationship scale (p<0.05) with its two domains [satisfaction and instrumental help (p<0.01)] and the total classroom community scale (p<0.05) with its domains [connectedness (p<0.01) and learning experience (p<0.05)] decreased the likelihood of cyber victimization and cyberaggression. However, perceived conflicting teacher relationships increased the likelihood of cyber victimization (p<0.05) and cyberaggression (p<0.01). Conclusion: Cyberbullying is a concern among university students, and the students’ perceived nature of their relationships with their teachers and sense of virtual classroom community play a pivotal role in shaping their involvement in cyberaggression and exposure to cyber victimization. Thus, developing mass media campaigns to enhance awareness about cyberbullying and cyber civility regulations is recommended.